"You are my rock and fortress". Refuge metaphors in Psalm 31. A perspective from cognitive metaphor theory - A. Basson (Acta Theologica)
The psalms of lamentation are prayers of a beleaguered individual or nation. The one under constant attack of the enemy has no other option but to implore the deity to intervene on his behalf. Yahweh is invoked to save the supplicant and to destroy the adversaries. Apart from this recurrent plea, Yahweh is often depicted as one providing refuge to those in need. Psalm 31 is no exception. The competent reader will identify various refuge metaphors being employed by the psalmist. Through the application of images from the natural world, the poet accentuates the notion that Yahweh acts as a refuge to his people. By taking recourse to the cognitive theory of metaphor, this study endeavours to explicate the cognitive world underlying the use of the refuge metaphors is Psalm 31.